Save Ocean: Development of a Mobile Game Application to Create Awareness on Ocean Pollution - Wee, Sung Yuan Natalie; A Hamid, Rahayu (Applied Information Technology And Computer Science, 2021)
In recent years, ocean pollution incidents have occurred frequently. This is not only a challenge faced by regions and countries only but also a problem that the global society needs to cope with. Every year, human abandoned eight million tons of plastic in the ocean. At this rate, the number of fish will be estimated less than plastic in the oceans during 2050. Next, ocean pollution is an environmental topic that has neglected by the majority of Malaysian. Thus, instilling an awareness of this issue should begin from the younger generation to improve their attitude. Hence, Save Ocean is a mobile game application developed to raise awareness of ocean pollution among children aged 6 to 12. This application is an adventure game which consists of 3 main levels and 15 sub-levels. Game Development Life Cycle has been applied as the methodology in designing and developing Save Ocean. There are 6 phases in this model, which are initiation phase, pre-production phase, production phase, testing phase, beta phase, and lastly, release phase. The game application is developed using Unity, Blender, Nomad Sculpt, Procreate, and CapCut. The overall result of the user acceptance test Save Ocean game application achieved a positive result with 87.6%. Hence, the target users can increase their knowledge about marine organisms after playing this game. Indirectly, it can create environmental awareness of ocean pollution to the users.